Ostraca Varia: Unpublished Deir el-Medina Ramesside Administrative Ostraca from the Ashmolean Museum, Oxford - Hudson, S. E..
The following article presents a small but varied group of unpublished Deir el-Medina nonliterary ostraca, dating to the Ramesside period, comprising an assortment of documentary types that spans both the collective and individual spheres of the community’s administration. Ashmolean HO 766 describes a domestic incident, and is identifiable as a s?3.w  text from the lego-judicial category, while Ashmolean HO 821, an accounting document provides fresh insights into the work and deliveries of the smd.t  water-carriers of the community, and Ashmolean HO 969, a fragmentary yet chronologically significant “journal-of-the-necropolis” text offers additional data on the accession date of Ramesses VI.